GENE MUTATION PATTERNS OF RIFAMPICIN IN MULTIDRUG RESISTANT MYCOBACTERIUM TUBERCULOSIS COMPLEX STRAINS - Esra Yıldırım Servi; Meltem Uzun (İstanbul Tıp Fakültesi Dergisi)
Objective: The aim of this study was to evaluate the GenoType®MTBDRplus test for detection of rifampicin (RIF) resistance in MDR Mycobacterium tuberculosis complex strains. Materials and Methods: Twenty-five multidrug-resistant (MDR) Mycobacterium tuberculosis clinical strains were used, gene mutations causing RIF resistance were investigated by GenoType®MTBDRplus and the results were compared with the results of the BACTEC 460 TB system. The strain was sequenced if there was no mutation and absence Wild Type (WT). Mycobacterium tuberculosis ATCC 35838 was used as a quality control (QC) strain. Results: There was 96% compliance between the GenoType®MTBDRplus and BACTEC 460 TB system for the finding of RIF resistance. The most frequent mutation zone in MDR strains was rpoB S531L promotor zone (13 strains, 52%). The other rpoB gene mutations were H526Y (three strains, 12%) and H526D (three strains, 12%), while five strains (20%) had Δ2-Δ5 mutations in the wild type probes. There was no mutation in only one strain (4%) by GenoType®MTBDRplus but it was found to be as resistant to rifampicin by the BACTEC 460 TB system. This strain was sequenced and detected to have triple mutations. Mutations were found on codons 489, 493, and 503. Conclusion: GenoType®MTBDRplus showed good compatibility with the BACTEC 460 TB system in detecting rifampicin resistance, and it was thought that GenoType®MTBDRplus could be an effective and reliable test for RIF susceptibility testing in MDRTB patients, providing a significant advantage in technical time.